The tree of life of copper-containing amine oxidases - Zhang, Zaibao; Xiong, Tao; Li, Kejia; Huang, Kexin; Wu, Siyu; Wu, Luhui (Frontiers in Plant Science, 2025)
Copper-containing amine oxidases (CuAOs) catalyze the terminal oxidation of polyamines (PAs), producing ammonium, an aminoaldehyde, and hydrogen peroxide (H2O2). Plant CuAOs are induced by stress-related hormones such as methyl-jasmonate (MeJA), abscisic acid (ABA), and salicylic acid (SA). Mammalian copper-containing amine oxidases (CAOs), encoded by four genes (AOC1-4) that catalyze the oxidation of primary amines to aldehydes, regulate various biological processes and are linked to diseases like inflammatory conditions and histamine intolerance. To understand the evolutionary history and functional divergence of CuAOs, we conducted phylogenetic and expression analyses of CuAOs in plants and animals. In this study, the copper amine oxidase (CuAO) genes were identified by HMMER and BLASTP, and verified by CDD/HMM/SMART. Multiple sequence alignment was performed using Muscle5, and the phylogenetic tree was constructed by IQ-TREE2. The syntenic relationship was analyzed by MCScanX and CIRCOS. Meanwhile, the expression data of Arabidopsis thaliana and human and other species were integrated for analysis. Here, 950 and 264 CuAO orthologues were identified in 188 plant and 79 animal genomes. Phylogenetic analyses indicate that CuAO originated in the common ancestor before the divergence of plants and animals. The copy numbers of CuAOs vary significantly across plant species, whereas they remain relatively stable in animal species, generally maintaining 3-4 copies per species. During the evolutionary process, plant CuAOs formed two clades (I and II), while animal CuAOs formed three clades (CAO-like, AOC1, AOC2-4). Interestingly, plant clade I CuAOs lacks the active site motif T/S-X1-X2-N-Y-D. The further differentiation of plant clade II CuAOs is related to the preference for X1 and X2 active sites. CAO-like and AOC1 are monophyletic branches. Mammalian AOC2-4 is separated from non-mammalian AOC2-4, and the differentiation of mammalian AOC3 and AOC4 occurs in a species-specific manner. Our study provides a comprehensive understanding of the evolutionary trajectory of the CuAO gene family in plants and animals at the genome-wide level. These findings lay a crucial foundation for future research to conduct in-depth functional characterization.